2010
DOI: 10.1007/s10488-009-0263-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-Discharge Services and Psychiatric Rehospitalization Among Children and Youth

Abstract: This study examined risk and determinants of rehospitalization of children and adolescents (n = 186) following a first psychiatric hospitalization. It specifically examined the role of post-discharge services. Data were collected for a 30-month follow-up period through structured telephone interviews with caregivers and case record abstractions. 43% of youth experienced readmissions during the follow-up period. Risk of rehospitalization was highest during the first 30 days following discharge and remained elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
92
4
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 47 publications
5
92
4
1
Order By: Relevance
“…For instance, only 2% of participants in this study failed to receive any treatment after being discharged from the hospital, compared to 28% in a study of hospitalized children and adolescents published by James et al in 2010. 10 Rates of treatment utilization among the current sample were also substantially higher than the two thirds reported by Daniel et al in 2004. 11 …”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…For instance, only 2% of participants in this study failed to receive any treatment after being discharged from the hospital, compared to 28% in a study of hospitalized children and adolescents published by James et al in 2010. 10 Rates of treatment utilization among the current sample were also substantially higher than the two thirds reported by Daniel et al in 2004. 11 …”
Section: Discussioncontrasting
confidence: 54%
“…8 The high rates of service use in these samples may be due to the fact that, unlike in the studies reviewed above, the participants were psychiatrically hospitalized, which suggests that they represented higher risk samples. Nonetheless, Spirito et al reported that, during a 3-month period after discharge, 18% terminated outpatient therapy against therapist advice, 9 and James et al found that, over a 30-month follow-up period, 28% of their sample of children and adolescents failed to receive any treatment following their first psychiatric hospitalization, 10 thus offering a less optimistic view of patterns of service use. In a review of data concerning children and adolescents who received inpatient psychiatric care, Daniel et al reported that, in general, two thirds or more of psychiatrically hospitalized youth received treatment of some kind following discharge from the hospital.…”
mentioning
confidence: 99%
“…The average youth psychiatric inpatient readmission rate ranges from 30% to 60% [15, 17, 18]. At least one-third of children and adolescents are more likely to be rehospitalized within the first 3 months to two years after the first admission [1517]. Those who are at a younger age at admission are generally more likely to be readmitted [17, 19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant number of adolescents continue to experience suicide-related outcomes after discharge, including rehospitalizations, emergency department visits (3), persistent suicidal ideation, and repeated suicidal behavior (47). Adolescent rehospitalization rates are high: 19%–28% are rehospitalized within six months (3,8), 38% within one year (9), and up to 43% within 2.5 years after discharge (10). The risk of rehospitalization is especially elevated during the first three months after discharge (911).…”
mentioning
confidence: 99%